2019
DOI: 10.3390/su11154116
|View full text |Cite
|
Sign up to set email alerts
|

Is Earnings Quality Associated with Corporate Social Responsibility? Evidence from the Korean Market

Abstract: Socially responsible firms are believed to behave in a responsible manner to restrict earnings management and thus deliver more reliable and transparent financial information to investors. We test this hypothesis by predicting a higher quality of financial reporting for socially responsible firms in the Korean market. The entire sample analysis provides evidence for the hypothesis in the use of discretionary accruals as proxy variables for the quality of financial reporting. However, our sub-sample analysis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…Thus overall, considering the above mentioned results, having two out of three validated hypotheses, it can be concluded that the adoption of the European Directive 2014/95/EU related to mandatory presentation of non-financial information led to a decrease in the use of earnings management practices by companies listed on the Bucharest Stock Exchange in the post-EUD period, 2017-2019, based on empirical evidence of exhibiting less income smoothing, in comparison to the pre-EUD period, 2015-2016. These findings are consistent with prior studies showing a negative association between nonfinancial reporting and earnings management [2], including in emerging economies [1,8].…”
Section: Regression Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus overall, considering the above mentioned results, having two out of three validated hypotheses, it can be concluded that the adoption of the European Directive 2014/95/EU related to mandatory presentation of non-financial information led to a decrease in the use of earnings management practices by companies listed on the Bucharest Stock Exchange in the post-EUD period, 2017-2019, based on empirical evidence of exhibiting less income smoothing, in comparison to the pre-EUD period, 2015-2016. These findings are consistent with prior studies showing a negative association between nonfinancial reporting and earnings management [2], including in emerging economies [1,8].…”
Section: Regression Resultssupporting
confidence: 92%
“…In addition, academic literature indicates that emerging markets are to some extent neglected, arguing that there is a necessity for this gap to be addressed [8]. Other research findings referring to developed countries cannot be extrapolated to developing contexts, considering that stakeholders in these settings affect differently the decisionmaking process related to release of non-financial reports [9].…”
Section: Particularities Of the Romanian Settingmentioning
confidence: 99%
“…and tends to have good earnings quality and provide longterm benefits (Calegari et al, 2010;Hong and Andersen. , 2011;Kim et al, 2012;Litt et al, 2014;Scholtens and Kang, 2013;Azis and Faisol, 2018).…”
Section: The Effect Of Csr Disclosure On Earnings Qualitymentioning
confidence: 99%
“…Several studies state that companies that are oriented towards social responsibility tend to have good earnings quality and provide long-term benefits (Calegari et al, 2010;Hong and Andersen, 2011;Kim et al, 2012;Scholtens and Kang, 2013;Litt et al, 2014). The indication that CSR disclosure is considered capable of changing stakeholders' views, especially in improving reputation and improving the quality of reports, indicates the possibility that CSR disclosure also has an indirect effect on earnings quality through accounting conservatism.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the connection of corporate governance to socially responsible actions has been thoroughly investigated in those studies. In addition, the relationship between corporate social responsibility and the management of earnings has also been quite frequently examined in different prior research projects (Gras-Gil et al, 2016;Chih, Shen, & Kang, 2008;Yoon, Kim, Lee, 2019;Suteja, Gunardi, & Mirawati, 2016;Sial, Chunmei, Khan, & Nguyen, 2018). Some of them tried to evaluate the impact of socially responsible activities on manipulating the earnings in accounting reports (Gras-Gil et al, 2016;Gavana et al, 2017;Chih et al, 2008;Yoon et al, 2019).…”
Section: Introduction 5mentioning
confidence: 99%